Kebijakan Utang dan Beberapa Faktor yang Mempengaruhi: Studi Kasus Perusahaan Pertambangan di Indonesia - Ari Maulana; Ghazali Syamni; H Husaini; J Jummaini (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2022)
This study examined the influence of dividend policy, asset structure, and managerial ownership on debt policy in mining companies listed on the Indonesian Stock Exchange. This study used secondary data obtained from the financial statements and annual reports of each company as many as 23 mining companies as the sample. The data analysis method used was a multiple linear regression analysis with the help of Eviews 10. The results partially showed that dividend policy and asset structure partially did not influence debt policy, while ownership partially positively and significantly influence debt policy. Meanwhile simultaneously, dividend policy, asset structure, and ownership affected the debt policy of mining companies listed on the Indonesia Stock Exchange.